THE REALIZATION OF INTERPERSONAL MEANING IN COURSE NEWSLETTERS: A SYSTEMIC FUNCTIONAL LINGUISTIC PERSPECTIVE - Yuliana, Dian; Imperiani, Ernie D.A. (Universitas Pendidikan Indonesia, 2017)
This study investigates the realizations of interpersonal meaning in newsletters offering online courses by general and Islamic educational institutions, and whether or not the realization of this strand of meaning by the two groups of institutions is similar. Twelve newsletters from six educational institutions (three general and three Islamic) offering online courses were used as the data. Using Halliday and Matthiessen’s (2004) grammar of interaction, the study found some similarities and differences in the realization of interpersonal meanings in the two groups of newsletters. Regarding the mood types, both institutions mostly use declaratives realizing the speech function of statement. Following this is imperative that is frequently employed to make offer and, in fewer frequency, command. The study also found that modalities and modulation are only used sparingly by both institutions. The dominant use of declaratives suggests that most of the writers of these newsletters provide information without creating an imagined dialogue with their readers. The relatively high use of offer in the data is hardly surprising due to the nature of the genres of newsletters. In addition, the small number of modality used in the newsletters demonstrates that the text producers prefer to present their propositions and proposals as facts.